2003
DOI: 10.1093/jn/133.1.78
|View full text |Cite
|
Sign up to set email alerts
|

The Serum LDL/HDL Cholesterol Ratio Is Influenced More Favorably by Exchanging Saturated with Unsaturated Fat Than by Reducing Saturated Fat in the Diet of Women

Abstract: We compared the effects of a high fat diet [38.4% of energy (E%) from fat; HSAFA diet, polyunsaturated/saturated fatty acid (P/S) ratio = 0.14], a low fat diet (19.7 E% from fat; LSAFA diet, P/S = 0.17), both based on coconut oil, and a diet with a high content of mono- and polyunsaturated fatty acids (PUFA; 38.2 E% from fat; HUFA diet, P/S = 1.9) on serum lipoproteins. The 25 women studied consumed each diet for 3-wk periods in a crossover design. The two high fat diets were identical except for the quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
5
7

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 37 publications
2
72
5
7
Order By: Relevance
“…An unexpected finding was the inverse relationship between saturated fatty acid intake and HDL-cholesterol concentration. These results are contradictory to those reported in previous studies (35)(36)(37), and we found no evident explanation.…”
Section: Discussioncontrasting
confidence: 99%
“…An unexpected finding was the inverse relationship between saturated fatty acid intake and HDL-cholesterol concentration. These results are contradictory to those reported in previous studies (35)(36)(37), and we found no evident explanation.…”
Section: Discussioncontrasting
confidence: 99%
“…This was confirmed by Hodson [16] and Müller [30], who observed favorable changes in the lipid profiles of participants who replaced in their diets products rich in saturated fats with products rich in unsaturated fats.…”
Section: Introductionsupporting
confidence: 61%
“…To positively impact HDL‐cholesterol, researchers suggest replacing saturated fat with unsaturated fat instead of decreasing overall fat intake (Muller et al. 2003), which was not a component of our study design.…”
Section: Resultsmentioning
confidence: 99%